Yolk vitamin E positively affects prenatal growth but not oxidative status in yellow-legged gull embryos. Issue 3 (23rd May 2017) - Parolini, Marco; Possenti, Cristina Daniela; Karadas, Filiz; Colombo, Graziano; Romano, Maria; Caprioli, Manuela; Dalle-Donne, Isabella; Rubolini, Diego; Milzani, Aldo; Saino, Nicola
Abstract: Parental effects occur whenever the phenotype of parents or the environment that they experience influences the phenotype and fitness of their offspring. In birds, parental effects are often mediated by the size and biochemical quality of the eggs in terms of maternally transferred components. Exogenous antioxidants are key egg components that accomplish crucial physiological functions during early life. Among these, vitamin E plays a vital role during prenatal development when the intense metabolism accompanying rapid embryo growth results in overproduction of pro-oxidant molecules. Studies of captive birds have demonstrated the positive effect of vitamin E supplementation on diverse phenotypic traits of hatchling and adult individuals, but its effects on embryo phenotype has never been investigated neither in captivity nor under a natural selection regime. In the present study, we experimentally tested the effect of the in ovo supplementation of vitamin E on morphological traits and oxidative status of yellow-legged gull ( Larus michahellis ) embryos. The supplementation of vitamin E promoted somatic growth in embryos soon before hatching, but did not affect their oxidative status. Our results suggest that maternally transferred vitamin E concentrations are optimized to prevent imbalances of oxidative status and the consequent raise of oxidative damage in yellow-legged gull embryos during prenatal development.